Color conversion film, luminescent device and preparation method thereof
By forming a hole structure in the quantum dot color conversion layer, the problem of shortening the service life of the quantum dot color conversion layer caused by heat of the Micro-LED light-emitting chip is solved, and the effect of reducing the working temperature and extending the service life is achieved.
Patent Information
- Application Number
- CN202311282232.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-04
AI Technical Summary
The heat generated by the Micro-LED light-emitting chip during operation causes the service life of the quantum dot color conversion layer to be shortened.
A hole structure that can dissipate heat is formed in the quantum dot color conversion layer, so that the heat generated by the light-emitting chip is transferred to the outside world along the hole, thereby reducing the adverse effects of heat on the quantum dot material.
Through the heat dissipation hole structure, the working temperature of the light-emitting chip is reduced and the service life of the light-emitting device is extended.
Smart Images

Figure CN119767902A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and more specifically, to a color conversion film, a light-emitting device and a preparation method thereof. Background Art
[0002] Micro-LED technology is considered to be the next generation of display technology in the field of consumer electronics. Its outstanding features such as high resolution, fast response, low energy consumption, and long life can meet the needs of ultra-small and ultra-large displays, such as virtual / enhanced display, and show great application potential. It has attracted extensive research in academia and industry. Although many companies have launched prototypes and application demonstrations based on Micro-LED display technology, Micro-LED display technology is far from mature. Micro-LED still faces technical challenges in chips, mass transfer, and full colorization. Currently, Micro-LEDs on the market generally achieve color conversion by depositing a quantum dot color conversion layer on the blue light chip, so that Micro-LED can emit light of different colors.
[0003] However, when the Micro-LED blue light chip under the quantum dot color conversion layer is normally lit, in addition to emitting high-brightness blue light, it also generates a large amount of heat, causing the temperature of the quantum dot color conversion layer on the blue light chip to continue to rise, greatly shortening the service life of the quantum dots in the film layer, thereby reducing the use effect of the Micro-LED light-emitting device. Summary of the invention
[0004] The technical problem to be solved by the present application is that the heat generated when the light-emitting chip is working causes the service life of the quantum dot color conversion layer to be shortened.
[0005] In order to solve the above technical problems, the present application provides a color conversion film, which adopts the following technical solution:
[0006] A color conversion film comprises a quantum dot color conversion layer, the material of the quantum dot color conversion layer comprises quantum dot material and a plasticizer, and the quantum dot color conversion layer has a hole structure.
[0007] Furthermore, the pore structure has a pore size of 1 to 50 nm; and / or,
[0008] The thickness of the quantum dot color conversion layer is 4 to 12 um; and / or,
[0009] The plasticizer includes one or more of polystyrene, polyvinyl alcohol, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate, and polyimide; and / or,
[0010] The quantum dot material includes one or more of silicon quantum dots, germanium quantum dots, sulfide quantum dots, selenide quantum dots, telluride quantum dots, phosphide quantum dots, and arsenide quantum dots; and / or,
[0011] The surface of the quantum dot material is bound with a ligand, and the ligand is selected from one or more of an acid ligand, a thiol ligand, an amine ligand, a phosphine ligand, an oxygen phosphine ligand, a phospholipid, a soft phosphine, polyvinyl pyridine and an aromatic phosphate compound;
[0012] Optionally, the acid ligand includes one or more of formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosanoic acid, tetracosanoic acid, hexacosanoic acid, oleic acid, stearic acid, linoleic acid, arachidic acid, arachidonic acid, erucic acid, docosahexaenoic acid, and benzoic acid;
[0013] Optionally, the thiol ligand is selected from one or more of methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, nonyl mercaptan, decyl mercaptan, undecanethiol, dodecanethiol, hexadecyl mercaptan, benzyl mercaptan and octadecyl mercaptan;
[0014] Optionally, the amine ligand is selected from one or more of methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dioctylamine, nonylamine, decylamine, dodecylamine, hexadecylamine, dimethylamine, diethylamine, dipropylamine, tributylamine, trioctylamine, oleylamine, octadecylamine, aniline, indenepropylamine, 4-octylaniline and benzidine;
[0015] Optionally, the phosphine ligand is selected from one or more of methyl phosphine, ethyl phosphine, propyl phosphine, butyl phosphine, pentyl phosphine, octyl phosphine, dioctyl phosphine, trimethyl phosphine, triethyl phosphine, tripropyl phosphine, tributyl phosphine, trioctyl phosphine, tridecyl phosphine, trihexyl phosphine and trinonyl phosphine;
[0016] Optionally, the phosphine oxide ligand is selected from one or more of tributylphosphine oxide, trioctylphosphine oxide, trihexylphosphine oxide, trioctylphosphine oxide, trinonylphosphine oxide, bis(2-diphenylphosphinoethyl)phenylphosphine and triphenylphosphine oxide;
[0017] Optionally, the aromatic phosphate compound includes one or more of tetraethyl p-xylene diphosphate and diphenyl ethyl phosphate. Further, the color conversion film also includes a barrier layer, and the barrier layer is stacked on the quantum dot color conversion layer.
[0018] Furthermore, the thickness of the barrier layer is 1 to 20 um; and / or,
[0019] The barrier layer comprises a thermally conductive material;
[0020] The thermally conductive material includes one or more of SiO2, Al2O3 and graphene.
[0021] In order to solve the above technical problems, the present application also provides a method for preparing a color conversion film, which adopts the following technical solution:
[0022] A method for preparing a color conversion film comprises the following steps:
[0023] Mixing quantum dot material, plasticizer and organic solvent to obtain a quantum dot mixed solution;
[0024] The quantum dot mixed solution is formed into a quantum dot color conversion layer by utilizing electrostatic spinning technology, and the quantum dot color conversion layer has a hole structure.
[0025] Further, the organic solvent includes a first solvent and a second solvent, and the first solvent and the second solvent have different boiling points;
[0026] The first solvent and the second solvent are independently selected from one or more of alkane solvents, alcohol solvents, ester solvents or aromatic hydrocarbon solvents.
[0027] Further, the boiling point difference between the first solvent and the second solvent is greater than or equal to 50°C;
[0028] And / or, the volume ratio of the first solvent to the second solvent is 1:(0.8-1).
[0029] Furthermore, in the quantum dot mixed solution, the quantum dot material is 15 to 20 parts, the organic solvent is 25 to 35 parts, and the plasticizer is 45 to 60 parts by weight; and / or,
[0030] The plasticizer includes one or more of polystyrene, polyvinyl alcohol, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate, and polyimide.
[0031] Furthermore, after the step of using the electrostatic spinning technology to form a quantum dot color conversion layer from the quantum dot mixed solution, the method further includes: preparing a barrier layer on the quantum dot color conversion layer; and / or,
[0032] The conditions of the electrospinning technology include: environmental humidity of 30-50% RH, electrospinning voltage range of 15-20 kV, solution injection rate range of 1-3 mL / h, solution injection distance range of 8-25 cm, injection needle inner diameter range of 0.2-2 mm, and the temperature of the quantum dot mixed solution during spinning is 40-60° C.
[0033] In order to solve the above technical problems, the embodiment of the present application further provides a light emitting device, which adopts the following technical solution:
[0034] A light-emitting device, wherein the light-emitting unit has a color conversion film on its light-emitting side, wherein the color conversion film is a color conversion film provided by any of the above schemes, or a color conversion film prepared by a preparation method of a color conversion film provided by any of the above schemes.
[0035] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0036] The present application forms a hole structure that can dissipate heat in the quantum dot color conversion layer, so that when the color conversion film is set on the light-emitting chip, the heat generated by the light-emitting chip can be transferred to the outside along the holes of the quantum dot color conversion layer to dissipate the heat, thereby reducing the adverse effects of the heat of the light-emitting chip on the quantum dot material, thereby reducing the operating temperature of the light-emitting device and extending the service life of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the scheme of the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0038] Figure 1 is a schematic diagram of the structure of a color conversion film provided by an embodiment of the present application;
[0039] Figure 2 is a flowchart of the steps of a method for preparing a color conversion film provided by an embodiment of the present application;
[0040] Figure 3 is a schematic structural diagram of a light-emitting device provided by an embodiment of the present application;
[0041] Reference numerals:
[0042] 100. quantum dot color conversion layer; 200. barrier layer; 300. light-emitting chip. DETAILED DESCRIPTION
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.
[0044] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0045] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.
[0046] See also Figure 1 The embodiment of the present application provides a color conversion film, including a quantum dot color conversion layer 100, wherein the material of the quantum dot color conversion layer 100 includes a quantum dot material and a plasticizer, and the quantum dot color conversion layer 100 has a hole structure.
[0047] The present application forms a hole structure that can dissipate heat in the quantum dot color conversion layer 100, so that when the color conversion film is set on the light-emitting chip 300, the heat generated by the light-emitting chip 300 can be transferred to the outside along the holes of the quantum dot color conversion layer 100 to dissipate heat, thereby reducing the adverse effects of the heat of the light-emitting chip 300 on the quantum dot material, thereby reducing the operating temperature of the light-emitting device, and playing a role in extending the service life of the light-emitting device.
[0048] In one embodiment, the pore size of the hole structure is 1nm to 50nm. It can be understood that the hole structure with a pore size of 1 to 50nm makes the hole structure in the quantum dot color conversion layer 100 mesopores, ensuring that the heat generated by the light-emitting chip 300 can be conducted to the outside through the mesopores. At the same time, the nano-scale mesopores have a small pore size, which can ensure the mechanical strength and stability of the quantum dot color conversion layer 100, thereby ensuring the stability of the color conversion film.
[0049] Specifically, in some embodiments, the pore size of the pore structure can be set to any one of 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, etc., or a range between any two of them. In this embodiment, the pore size range of the hole structure is preferably 30nm to 40nm. The reason is that the pore size of the hole structure affects the heat conduction effect within this range but does not affect the luminous brightness. When the pore size is less than 30nm, the heat conduction effect will be affected, and the heat cannot be effectively conducted to the outside. If the pore size is greater than 40nm, the luminous effect will be reduced. An excessively large pore size will cause the blue light emitted by the blue light chip to penetrate to the outside without being absorbed by the quantum dots, resulting in a reduction in the brightness of the light color emitted by the quantum dot color conversion layer 100.
[0050] In this embodiment, the hole structure of the quantum dot color conversion layer 100 is processed by electrospinning technology.
[0051] In one embodiment, the thickness of the quantum dot color conversion layer 100 is 4um to 12um. It is understandable that the quantum dot color conversion layer 100 can take into account the rigidity of the film layer and the size requirements of the light-emitting device within this thickness range. Specifically, if the quantum dot color conversion layer 100 is too thin, the mechanical strength of the film layer with a hole structure will decrease, which will affect the preparation of the subsequent light-emitting device; if the quantum dot color conversion layer 100 is too thick, it will be detrimental to the miniaturization of the light-emitting device.
[0052] Specifically, in some embodiments, the thickness of the quantum dot color conversion layer 100 can be set to any one or any two of 4um, 5um, 6um, 7um, 7um, 7.1um, 7.2um, 7.3um, 7.4um, 7.5um, 7.6um, 7.7um, 7.8um, 7.9um, 8um, 8.1um, 8.2um, 8.3um, 8.4um, 8.5um, 8.6um, 8.7um, 8.8um, 8.9um, 9um, 10um, 11um, 12um, etc. In this embodiment, the thickness of the quantum dot color conversion layer 100 is preferably 7 to 9um, which takes into account the rigidity of the film layer and adapts to the size requirements of the light-emitting device, and is more conducive to heat dissipation.
[0053] In one embodiment, the plasticizer is selected from one or more of polystyrene, polyvinyl alcohol, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate, and polyimide. It is understandable that the plasticizer described in the present application refers to a polymer that can cure and fix the quantum dot material. By using one or more of the above polymers as plasticizers, the quantum dot color conversion layer 100 can have a pore structure after curing and forming, and at the same time have good mechanical strength; the polymer has good plasticity, which is conducive to the formation of the pore structure, and has strong corrosion resistance, so that the pore structure is not easily destroyed by other film layers after formation, thereby improving the reliability of the preparation process.
[0054] In this embodiment, the quantum dot material is one or more of silicon quantum dots, germanium quantum dots, sulfide quantum dots, selenide quantum dots, telluride quantum dots, phosphide quantum dots, arsenide quantum dots and copper indium sulfide quantum dots.
[0055] Specifically, the quantum dot material is selected from at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound;
[0056] Wherein, the II-VI Group compound is selected from at least one of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe;
[0057] The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe;
[0058] The III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb;
[0059] The I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2;
[0060] The core of the core-shell structured quantum dots includes any one of the single structured quantum dots, and the shell material of the core-shell structured quantum dots is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and single structured quantum dots.
[0061] In this embodiment, a ligand is bound to the surface of the quantum dot material, and the ligand is selected from one or more of an amino group, a thiol group, a carboxyl group, and a hydroxyl group.
[0062] It can be understood that the ligand is selected from one or more of acid ligands, thiol ligands, amine ligands, phosphine ligands, phosphine oxide ligands, phospholipids, phospholipids, polyvinyl pyridine and aromatic phosphate compounds;
[0063] Optionally, the acid ligand includes one or more of formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosanoic acid, tetracosanoic acid, hexacosanoic acid, oleic acid, stearic acid, linoleic acid, arachidic acid, arachidonic acid, erucic acid, docosahexaenoic acid, and benzoic acid;
[0064] Optionally, the thiol ligand is selected from one or more of methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, nonyl mercaptan, decyl mercaptan, undecanethiol, dodecanethiol, hexadecyl mercaptan, benzyl mercaptan and octadecyl mercaptan;
[0065] Optionally, the amine ligand is selected from one or more of methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dioctylamine, nonylamine, decylamine, dodecylamine, hexadecylamine, dimethylamine, diethylamine, dipropylamine, tributylamine, trioctylamine, oleylamine, octadecylamine, aniline, indenepropylamine, 4-octylaniline and benzidine;
[0066] Optionally, the phosphine ligand is selected from one or more of methyl phosphine, ethyl phosphine, propyl phosphine, butyl phosphine, pentyl phosphine, octyl phosphine, dioctyl phosphine, trimethyl phosphine, triethyl phosphine, tripropyl phosphine, tributyl phosphine, trioctyl phosphine, tridecyl phosphine, trihexyl phosphine and trinonyl phosphine;
[0067] Optionally, the phosphine oxide ligand is selected from one or more of tributylphosphine oxide, trioctylphosphine oxide, trihexylphosphine oxide, trioctylphosphine oxide, trinonylphosphine oxide, bis(2-diphenylphosphinoethyl)phenylphosphine and triphenylphosphine oxide;
[0068] Optionally, the aromatic phosphate compound includes one or more of tetraethyl p-xylene diphosphate and ethyl diphenyl phosphate.
[0069] It can be understood that the ligands bound to the surface of the quantum dot material can improve the stability of the quantum dots in the quantum dot mixed solution.
[0070] In this embodiment, the color conversion film further includes a barrier layer 200 , and the barrier layer 200 is stacked on the quantum dot color conversion layer 100 .
[0071] A barrier layer 200 is deposited on the light-emitting side of the quantum dot color conversion layer 100. The barrier layer 200 can prevent external water and oxygen from entering the color conversion layer to avoid quantum dot failure, thereby increasing the service life of the quantum dot color conversion layer 100 and achieving the effect of extending the service life of the light-emitting device.
[0072] Specifically, the barrier layer 200 is disposed on a side of the quantum dot color conversion layer 100 away from the light emitting chip 300 , so that the quantum dot color conversion layer 100 is separated from the outside by the barrier layer 200 , and can also play an anti-scratch role.
[0073] In the present embodiment, when the quantum dot color conversion layer 100 is prepared by electrospinning technology, the surface of the quantum dot color conversion layer 100 will be smooth, and mirror reflection will be formed on the surface of the quantum dot color conversion layer 100, thereby affecting the light output effect. In the present embodiment, a barrier layer 200 is set in the quantum dot color conversion layer 100, and the mirror reflection can be reduced by increasing the roughness of the barrier layer 200, thereby improving the light output uniformity of the light-emitting device.
[0074] In this embodiment, the thickness of the barrier layer 200 is 2-3um. Specifically, the thickness of the barrier layer 200 can be set to any one of 2um, 2.1um, 2.2um, 2.3um, 2.4um, 2.5um, 2.6um, 2.7um, 2.8um, 2.9um, 3um, etc. or a range between any two. In this thickness range, it is beneficial for the heat of the barrier layer 200 to be transferred to the outside world. At the same time, the water and oxygen barrier layer 200 can also isolate the external water and oxygen from entering the quantum dot color conversion layer 100, causing the quantum dots to fail, and protect the color conversion layer to play an anti-scratch role.
[0075] In this embodiment, the barrier layer 200 is made of a thermally conductive material. It can be understood that the use of a thermally conductive material to prepare the barrier layer 200 can, on the one hand, play a role in blocking water and oxygen, and on the other hand, the barrier layer 200 with thermal conductivity can allow the hole structure of the quantum dot color conversion layer 100 to conduct heat to the barrier layer 200, and transfer and dissipate it to the outside, thereby avoiding excessive heat from the quantum dot color conversion layer 100 to damage the performance of the quantum dots.
[0076] Specifically, the thermal conductive material is selected from one or more of SiO2, Al2O3 and graphene. Specifically, the barrier layer 200 is prepared using the barrier layer 200 material provided above, so that the barrier layer 200 has a certain water and oxygen barrier ability, and also has good thermal conductivity, and the prepared barrier layer 200 can have an appropriate roughness, which can simultaneously improve the light emitting effect of the light emitting device and extend the service life of the light emitting device.
[0077] See also Figure 2 Based on the above color conversion film, the present application embodiment further provides a method for preparing the color conversion film, the method comprising:
[0078] S100, mixing a quantum dot material, a plasticizer and an organic solvent to obtain a quantum dot mixed solution;
[0079] S200 , using electrostatic spinning technology to form a quantum dot color conversion layer 100 from the quantum dot mixed solution, wherein the quantum dot color conversion layer 100 has a hole structure.
[0080] In this embodiment, the organic solvent in the quantum dot mixed solution is volatilized during the spinning process by utilizing electrospinning technology, resulting in phase separation. By controlling the corresponding electrospinning conditions, after the organic solvent in the quantum dot mixed solution is volatilized, the quantum dot material and the plasticizer are solidified to obtain a quantum dot color conversion layer 100 having a hole structure. The quantum dot color conversion layer 100 is a nanofiber having a hole structure, which can transfer the heat on the light-emitting chip 300 to the outside through the hole structure, effectively reducing the temperature of the light-emitting device and the film temperature of the quantum dot color conversion layer 100, and extending the service life of the light-emitting device and the quantum dot color conversion layer 100.
[0081] In this embodiment, in the quantum dot mixed solution, the quantum dot material is 15 to 20 parts, the organic solvent is 25 to 35 parts, and the plasticizer is 45 to 60 parts, by weight.
[0082] Specifically, in the quantum dot mixed solution, the quantum dot material is 15 to 17 parts, the organic solvent is 25 to 30 parts, and the plasticizer is 53 to 60 parts, by weight; or, the quantum dot material is 18 to 20 parts, the organic solvent is 30 to 35 parts, and the plasticizer is 45 to 52 parts; or, the quantum dot material is 16 to 18 parts, the organic solvent is 27 to 34 parts, and the plasticizer is 48 to 57 parts.
[0083] In this embodiment, after step S200, the following steps are further included:
[0084] S300 , preparing a barrier layer 200 on the quantum dot color conversion layer 100 .
[0085] The barrier layer 200 is prepared by magnetron sputtering. Specifically, the barrier layer 200 prepared by this method can increase the roughness of the surface of the barrier layer 200, and the barrier layer 200 disposed on the quantum dot color conversion layer 100 can improve the reflection effect of the quantum dot color conversion layer 100, thereby improving the light extraction efficiency of the light emitting device.
[0086] In this embodiment, the organic solvent includes a first solvent and a second solvent, and the first solvent and the second solvent have different boiling points. Specifically, by using two organic solvents with different boiling points, the quantum dot mixed solution undergoes phase separation during the electrospinning process, and the first solvent and the second solvent have different evaporation rates due to their different boiling points, which is conducive to forming more uniform pore sizes.
[0087] It can be understood that when the boiling point of the first solvent is lower than that of the second solvent, during the electrospinning process of the quantum dot mixed solution, the first solvent evaporates first, and the evaporation to the outside causes the plasticizer to form rough holes of different sizes inside during the curing process. Since the second solvent has a higher boiling point and evaporates more slowly, the second solvent will evaporate along the holes of different sizes formed by the evaporation of the first solvent and enter the outside, so that the smaller pore size is enlarged, and finally the pore size tends to be consistent. This embodiment uses two organic solvents with different boiling points to avoid the problem of poor uniformity of the pore size of the obtained quantum dot color conversion layer 100, and prevent the pore structure of different sizes from having an adverse effect on the luminescence uniformity of the quantum dot color conversion layer 100.
[0088] In this embodiment, the first solvent and the second solvent are independently selected from one or more of alkane solvents, alcohol solvents, ester solvents or aromatic hydrocarbon solvents.
[0089] Wherein, the alkane solvent is selected from at least one of hexane, octane, decane and alkanes with higher boiling points;
[0090] The alcohol solvent is selected from at least one of a monohydric alcohol and a dihydric alcohol;
[0091] The monohydric alcohol includes amyl alcohol, isopentanol, secondary amyl alcohol, secondary isopentanol, 3-pentanol, tert-pentanol, cyclopentanol, 2-methylpentanol, 4-methyl-2-pentanol, n-hexanol, 2-methylpentanol, 2-methyl-2-pentanol, 2-methyl-3-pentanol, 3-ethyl-3-pentanol, n-heptanol, 2-heptanol, 3-heptanol, 2-ethylhexanol, 2-methylcyclohexanol, n-octanol, 2-octanol, 3,5,5-trimethylhexanol, nonanol, 2,6-dimethyl-4-heptanol, n-decanol, 5-ethyl-2-nonanol, undecanol, 5-ethyl-2-nonanol, dodecanol (lauryl alcohol), trimethylnonanol, cis-2-methylcyclohexanol, cis-3-methylcyclohexanol, cis-4-methylcycloethanol, 2-butoxyethanol, benzyl alcohol, benzhydrol, α-phenylethanol, β-phenylethanol;
[0092] The diols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 2,2-dimethyl-1,3-propylene glycol, 2-butene-1,4-diol, 2-methyl-2,4-pentanediol, 2,3-dimethyl-2,3-butylene glycol, 2-ethyl-1,3-hexanediol, 1,2,4-butanetriol, 1,2,6-hexanetriol, and pentaerythritol.
[0093] The ester solvent is selected from at least one of isopentyl butyrate, butyl valerate, amyl valerate, isopentyl isovalerate, butyl stearate, methyl benzoate, ethyl benzoate, propyl benzoate, isopropyl benzoate, butyl benzoate, isopentyl benzoate, ethyl phenylacetate, diethyl succinate, and diethyl adipate.
[0094] The aromatic hydrocarbon solvent is at least one of benzene, toluene, xylene and an alkylbenzene with a higher boiling point.
[0095] In this embodiment, the boiling point difference between the first solvent and the second solvent is greater than or equal to 50° C. Specifically, the boiling point of the first solvent is greater than the boiling point of the second solvent. Within this boiling point difference range, the first solvent and the second solvent are conducive to a significant difference in volatilization speed, thereby ensuring the uniformity of the pore size of the pore structure.
[0096] In some embodiments, the volume ratio of the first solvent to the second solvent is 1:(0.8-1). At this volume ratio, the first solvent and the second solvent are more conducive to producing a significant difference in volatilization rate under the aforementioned boiling point difference, thereby ensuring the pore size uniformity of the pore structure.
[0097] In this embodiment, in S200, the conditions of the electrospinning technology include: the ambient humidity is 30-50% RH.
[0098] Specifically, the ambient humidity can be set to 30% RH, 31% RH, 32% RH, 33% RH, 34% RH, 35% RH, 36% RH, 37% RH, 38% RH, 39% RH, 40% RH, 41% RH, 42% RH, 43% RH, 44% RH, 45% RH, 46% RH, 47% RH, 48% RH, 49% RH or 50% RH.
[0099] It is understandable that in the electrospinning technology, the thickness of the quantum dot color conversion layer 100 and the size of the internal pores can be changed by changing the conditions of electrospinning. Among them, the ambient humidity is an important factor affecting the formation of the pore structure. The ambient humidity mainly changes the pore size of the quantum dot color conversion layer 100 by affecting the volatilization rate of the organic solvent: when the ambient humidity is lower than 30% RH, the organic solvent evaporates quickly, and the pore size of the pore structure on the membrane layer is small; when the ambient humidity exceeds 30% RH, the surface pore structure of the quantum dot color conversion layer 100 is more obvious, and its number and diameter increase with the increase of ambient humidity, and the distribution density of the pores also increases accordingly; however, when the humidity is too high, the ambient humidity exceeds 50% RH, the volatilization rate of the organic solvent is slow, and before the organic solvent evaporates, it will gather together to cause the fibers to bond, resulting in excessively large pores formed on the surface, thereby weakening the mechanical strength of the color conversion layer.
[0100] The ambient humidity is in the range of 30-50% RH, which is conducive to the quantum dot color conversion layer 100 having a three-dimensional ordered hole structure after curing, and the formed holes are mesopores with a pore size of 30-40nm, which is conducive to the heat generated by the light-emitting chip 300 being conducted to the outside through the hole structure, while ensuring the mechanical strength and stability of the color conversion layer film structure.
[0101] In this embodiment, the conditions of the electrospinning technology also include: the electrospinning voltage range is 15 to 20 kV, the solution injection rate range is 1 to 3 mL / h, the solution injection distance range is 8 to 25 cm, the inner diameter range of the injection needle is 0.2 to 2 mm, and the temperature of the quantum dot mixed solution during spinning is 40 to 60°C.
[0102] Specifically, the conditions of the electrospinning technology can be set as follows: the electrospinning voltage range is 15-18 kV, the solution injection rate range is 1-2 mL / h, the solution injection distance range is 8-20 cm, and the injection needle inner diameter range is 0.2-1 mm; or,
[0103] The electrospinning voltage ranges from 18 to 20 kV, the solution injection rate ranges from 2 to 3 mL / h, the solution injection distance ranges from 20 to 25 cm, and the injection needle inner diameter ranges from 1 to 2 mm.
[0104] Under the conditions of the above-mentioned electrospinning technology, it is possible to ensure that a quantum dot film layer having a three-dimensional ordered pore structure is prepared by the electrospinning technology, and the pore size uniformity of the formed pores is high.
[0105] The present invention will be further described below in conjunction with specific embodiments:
[0106] Embodiment 1:
[0107] The method for preparing the color conversion film of this embodiment is as follows:
[0108] Step 1: 15 wt% of CdZnSe / ZnS quantum dot material, 15 wt% of ethyl acetate (boiling point 77° C.), 15 wt% of diethylbenzene (boiling point 180° C.), and 55 wt% of PMMA are mixed to obtain a quantum dot mixed solution;
[0109] Step 2: Place the quantum dot mixed solution into the injection device of the electrospinning equipment for spinning, adjust the voltage to 18 kV, the solution injection rate range to 2 mL / h, the solution injection distance range to 15 cm, the inner diameter of the injection needle tube to 2 mm, and the ambient humidity to 30% RH. The quantum dot spinning solution at room temperature in the electrospinning equipment is heated to 55°C. The heated quantum dot spinning solution is sprayed on the micro LED blue light substrate to prepare a quantum dot color conversion layer, and a quantum dot color conversion layer with a pore structure of 30 nm in diameter and a film thickness of 8 um is obtained.
[0110] Step 3: Deposit a SiO2 barrier layer on the quantum dot color conversion layer by magnetron sputtering, and the film thickness of the barrier layer is 2 um.
[0111] Example 2
[0112] The color conversion film preparation method of this embodiment is different from that of embodiment 1 in that:
[0113] The ambient humidity in step 2 was changed to 50% RH to obtain a quantum dot color conversion layer with a pore structure diameter of 40 nm and a film thickness of 8 um.
[0114] Example 3
[0115] The color conversion film preparation method of this embodiment is different from that of embodiment 1 in that:
[0116] The water and oxygen barrier layer material deposited in step 3 is Al2O3, and the film thickness is 2um.
[0117] Example 4
[0118] Step 1: 15 wt% of CdZnSe / ZnS quantum dot material, 15 wt% of n-octane (boiling point 125° C.), 15 wt% of diethylene glycol butyl ether acetate (boiling point 246° C.), and 55 wt% of PMMA are mixed to obtain a quantum dot mixed solution;
[0119] Step 2: Place the quantum dot mixed solution into the injection device of the electrospinning equipment for spinning, adjust the voltage to 18 kV, the solution injection rate range to 2 mL / h, the solution injection distance range to 15 cm, the injection needle inner diameter to 2 mm, and the ambient humidity to 30% RH. The quantum dot spinning solution at room temperature is heated to 85°C in the electrospinning equipment. The heated quantum dot spinning solution is sprayed on the micro LED blue light substrate to prepare a quantum dot color conversion layer, and a quantum dot color conversion layer with an aperture structure of 33 nm and a film thickness of 8 um is obtained.
[0120] Step 3: Deposit a SiO2 water-oxygen barrier layer on the quantum dot color conversion layer using magnetron sputtering, with a film thickness of 2 um.
[0121] Example 5
[0122] The color conversion film preparation method of this embodiment is different from that of embodiment 1 in that:
[0123] The plasticizer in step 1 is 2,2-bis(4-hydroxyphenyl)propane polycarbonate (CAS No. 25037-45-0, molecular formula C 31 H 32 O7), and a quantum dot color conversion layer with a hole structure diameter of 32nm and a film thickness of 8um was obtained.
[0124] Example 6
[0125] The color conversion film preparation method of this embodiment is different from that of embodiment 1 in that:
[0126] The plasticizer in step 1 is a polyimide resin (CAS No. 62929-02-6, molecular formula C 35 H 28 N2O7), and a quantum dot color conversion layer with a pore structure of 31nm and a film thickness of 8um was obtained.
[0127] Comparative Example 1
[0128] Step 1: 15 wt% of CdZnSe / ZnS quantum dot material, 15 wt% of ethyl acetate (boiling point 77° C.), 15 wt% of diethylbenzene (boiling point 180° C.), and 55 wt% of PMMA are mixed to obtain a quantum dot solution;
[0129] Step 2: Deposit the quantum dot solution on the micro LED blue light substrate by inkjet printing, and dry it at 180°C for 30 minutes to obtain a quantum dot color conversion layer with a thickness of 8um and no hole structure.
[0130] In this comparative example 1, during the electrospinning process, the quantum dot spinning solution is deposited on the micro On the LED blue light substrate, during the spraying process, the equipment will heat the quantum dot mixed solution. After heating, the temperature of the sprayed quantum dot mixed solution is 55°C. The solution obtains energy when heated, which intensifies the movement of molecules when the solvent evaporates, so that the quantum dot mixed solution begins to evaporate and phase separates from PMMA from the moment it leaves the nozzle, gradually forming holes in the filamentous nanofibers. In the process of the filamentous nanofibers being accumulated into a film on the substrate, the solvent continues to evaporate rapidly to obtain a quantum dot color conversion layer with a hole structure. In the process of inkjet printing, the quantum dot solution is deposited on the substrate in the form of ink droplets. The process is very fast. During this process, the temperature of the ink droplets is close to room temperature. The solvent can only evaporate naturally, and the process is slow and the amount of evaporation is small. In the process of ink droplets gathering into a micron-level film layer, the solvent can only evaporate slowly and naturally. The intensity of the diffusion of solvent molecules is not enough to form holes inside PMMA. Even at 180°C for 30 minutes, since the thickness of the formed film layer is at the micron level, the solvent is heated to accelerate the volatilization to form holes inside, and it will collapse instantly, resulting in the formed quantum dot color conversion layer having no hole structure.
[0131] Comparative Example 2
[0132] The color conversion film preparation method of this comparative example is different from that of Example 1 in that:
[0133] No water and oxygen barrier layer was prepared, and a quantum dot color conversion layer with a pore size of 30 nm and a film thickness of 8 um was obtained.
[0134] Comparative Example 3
[0135] The color conversion film preparation method of this comparative example is different from that of Example 1 in that:
[0136] The first solvent in step 1 is n-octane (boiling point 125°C), and the second solvent is propylene glycol methyl ether acetate (boiling point 145°C), and a quantum dot color conversion layer with a film thickness of 8um is obtained. Since the boiling point difference between the first solvent and the second solvent is less than 50°C, an azeotrope is formed during volatilization, and no difference in volatilization rate occurs, resulting in uneven pore size of the formed pore structure. The pore sizes of these pores vary, ranging from 25 to 32nm.
[0137] Comparative Example 4
[0138] The color conversion film preparation method of this comparative example is different from that of Example 1 in that:
[0139] The ambient humidity in step 2 was changed to 20% RH to obtain a quantum dot color conversion layer with a pore structure diameter of 23 nm and a film thickness of 8 um.
[0140] Comparative Example 5
[0141] The color conversion film preparation method of this comparative example is different from that of Example 1 in that:
[0142] The ambient humidity in step 2 was changed to 60% RH to obtain a quantum dot color conversion layer with a pore structure diameter of 51 nm and a film thickness of 8 um.
[0143] The quantum dot color conversion films of the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 5 of the present application are directly covered on the micro LED blue light chip of the micro LED blue light substrate during preparation, and then a water and oxygen barrier layer is prepared on the color conversion film (except for Comparative Example 2) to obtain light-emitting devices of other colors. The performance of these light-emitting devices is tested below to illustrate the role of the quantum dot color conversion film provided by the present application. Specifically, the light-emitting devices prepared in Examples 1-5 and Comparative Examples 1-5 are tested for performance according to the following test method:
[0144] 1. The test method for service life is: under the drive of constant current, the photoluminescence life of each light-emitting device is analyzed, and the time required for each light-emitting device to decay from the maximum brightness to 95% (T95, h) is recorded.
[0145] 2. Use a color luminance meter to test the maximum brightness Lmax of each device under normal lighting.
[0146] 3. Use an infrared temperature gun to measure the surface temperature of the device when it is working normally.
[0147] The test results are shown in Table 1:
[0148]
[0149]
[0150] According to the above test results:
[0151] 1. Compared with the light-emitting device of comparative example 1, the light-emitting devices of examples 1, 2, 3 and 4 have lower operating temperatures on the device surface under normal lighting conditions, indicating that the quantum dot color conversion layer with a hole structure can effectively conduct the heat generated on the microLED blue light substrate to the outside. Different plasticizers are used in examples 5 and 6, which can also effectively conduct the heat generated on the microLED blue light substrate to the outside.
[0152] 2. The light-emitting devices of Example 1, Example 2, Example 3 and Example 4 have a longer service life than that of Comparative Example 1, indicating that the service life of the micro-LED quantum dot color conversion layer can be significantly improved by preparing a hole structure quantum dot color conversion layer, thereby improving the use effect of the device. Different plasticizers are used in Example 5 and Example 6, and they also have a longer service life than that of Comparative Example 1;
[0153] 3. Compared with the light-emitting device of comparative example 2, the light-emitting device of embodiment 1 has a longer service life, which indicates that the setting of the barrier layer can effectively prevent external water and oxygen from entering the quantum dot color conversion layer, thereby improving the service life of the light-emitting device and having little effect on the brightness.
[0154] 4. Compared with the light-emitting device of comparative example 3, the light-emitting device of embodiment 1 has a longer service life and a lower operating temperature on the device surface, indicating that when the boiling point difference between the first solvent and the second solvent is greater than 50°C, it is beneficial for the quantum dot color conversion layer to form a hole structure with a more uniform pore size. Such a hole structure can better improve the heat dissipation effect of the light-emitting device and extend the service life, while basically having no effect on the brightness.
[0155] 5. Compared with the light-emitting device of comparative example 4, the light-emitting device of embodiment 1 has a longer service life and a lower operating temperature on the device surface, indicating that when the aperture of the hole structure is too small, the heat dissipation effect of the quantum dot color conversion layer will be reduced.
[0156] 6. Compared with the light-emitting device of Example 1 and the light-emitting device of Comparative Example 5, although the service life and the operating temperature of the device surface are not much different, when the aperture of the hole structure is too large, the maximum brightness under normal light emission will decrease, affecting the light-emitting brightness of the light-emitting device.
[0157] See also Figure 3 Based on the above-mentioned color conversion film, the present application also provides a light-emitting device, wherein the light-emitting side of the light-emitting device has a color conversion film, the color conversion film includes a quantum dot color conversion layer, the material of the quantum dot color conversion layer includes quantum dot material and a plasticizer, and the quantum dot color conversion layer has a hole structure.
[0158] Specifically, the light emitting device is a blue light chip, which includes a substrate and a blue light source disposed on the substrate, and a color conversion film is disposed on the substrate and covers the light emitting side of the blue light source.
[0159] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.
Claims
1. A color conversion film, characterized in that: It comprises a quantum dot color conversion layer, the material of the quantum dot color conversion layer comprises quantum dot material and a plasticizer, and the quantum dot color conversion layer has a hole structure.
2. The color conversion film according to claim 1, characterized in that: The pore structure has a pore diameter of 1 to 50 nm; and / or, The thickness of the quantum dot color conversion layer is 4 to 12 um; and / or, The plasticizer includes one or more of polystyrene, polyvinyl alcohol, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate, and polyimide; and / or, The quantum dot material includes one or more of silicon quantum dots, germanium quantum dots, sulfide quantum dots, selenide quantum dots, telluride quantum dots, phosphide quantum dots, and arsenide quantum dots; and / or, The surface of the quantum dot material is bound with a ligand, and the ligand is selected from one or more of an acid ligand, a thiol ligand, an amine ligand, a phosphine ligand, an oxygen phosphine ligand, a phospholipid, a soft phosphine, polyvinyl pyridine and an aromatic phosphate compound; Optionally, the acid ligand includes one or more of formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosanoic acid, tetracosanoic acid, hexacosanoic acid, oleic acid, stearic acid, linoleic acid, arachidic acid, arachidonic acid, erucic acid, docosahexaenoic acid, and benzoic acid; Optionally, the thiol ligand is selected from one or more of methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, nonyl mercaptan, decyl mercaptan, undecanethiol, dodecanethiol, hexadecyl mercaptan, benzyl mercaptan and octadecyl mercaptan; Optionally, the amine ligand is selected from one or more of methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dioctylamine, nonylamine, decylamine, dodecylamine, hexadecylamine, dimethylamine, diethylamine, dipropylamine, tributylamine, trioctylamine, oleylamine, octadecylamine, aniline, indenepropylamine, 4-octylaniline and benzidine; Optionally, the phosphine ligand is selected from one or more of methyl phosphine, ethyl phosphine, propyl phosphine, butyl phosphine, pentyl phosphine, octyl phosphine, dioctyl phosphine, trimethyl phosphine, triethyl phosphine, tripropyl phosphine, tributyl phosphine, trioctyl phosphine, tridecyl phosphine, trihexyl phosphine and trinonyl phosphine; Optionally, the phosphine oxide ligand is selected from one or more of tributylphosphine oxide, trioctylphosphine oxide, trihexylphosphine oxide, trioctylphosphine oxide, trinonylphosphine oxide, bis(2-diphenylphosphinoethyl)phenylphosphine and triphenylphosphine oxide; Optionally, the aromatic phosphate compound includes one or more of tetraethyl p-xylene diphosphate and ethyl diphenyl phosphate.
3. The color conversion film according to claim 1 or 2, characterized in that: The color conversion film further includes a barrier layer, and the barrier layer stack is arranged on the quantum dot color conversion layer.
4. The color conversion film according to claim 3, characterized in that: The thickness of the barrier layer is 1 to 20 um; and / or, The barrier layer comprises a thermally conductive material; The thermally conductive material includes one or more of SiO2, Al2O3 and graphene.
5. A method for preparing a color conversion film, characterized in that: The following steps are involved: Mixing quantum dot material, plasticizer and organic solvent to obtain a quantum dot mixed solution; The quantum dot mixed solution is formed into a quantum dot color conversion layer by utilizing electrostatic spinning technology, and the quantum dot color conversion layer has a hole structure.
6. The method for preparing a color conversion film according to claim 5, characterized in that: The organic solvent comprises a first solvent and a second solvent, and the first solvent and the second solvent have different boiling points; The first solvent and the second solvent are independently selected from one or more of alkane solvents, alcohol solvents, ester solvents or aromatic hydrocarbon solvents.
7. The method for preparing a color conversion film according to claim 6, characterized in that: The difference in boiling points between the first solvent and the second solvent is greater than or equal to 50° C.; And / or, the volume ratio of the first solvent to the second solvent is 1:(0.8-1).
8. The method for preparing a color conversion film according to any one of claims 5 to 7, characterized in that: In the quantum dot mixed solution, the quantum dot material is 15 to 20 parts, the organic solvent is 25 to 35 parts, and the plasticizer is 45 to 60 parts by weight; and / or, The plasticizer includes one or more of polystyrene, polyvinyl alcohol, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate, and polyimide.
9. The method for preparing a color conversion film according to any one of claims 5 to 7, characterized in that: After the step of using the electrostatic spinning technology to form a quantum dot color conversion layer from the quantum dot mixed solution, the method further includes: Preparing a barrier layer on the quantum dot color conversion layer; and / or, The conditions of the electrospinning technology include: environmental humidity of 30-50% RH, electrospinning voltage range of 15-20 kV, solution injection rate range of 1-3 mL / h, solution injection distance range of 8-25 cm, injection needle inner diameter range of 0.2-2 mm, and the temperature of the quantum dot mixed solution during spinning is 40-60° C.
10. A light emitting device, characterized in that: The light-emitting device has a color conversion film on its light-emitting side. The color conversion film is the color conversion film as claimed in any one of claims 1 to 4, or a color conversion film prepared by the method for preparing a color conversion film as claimed in any one of claims 5 to 9.
Citation Information
Patent Citations
Heat-resistant and high-tenacity ultrafine fibrous separation layer, method for manufacturing same, and secondary cell using same
CN102668173A
Patterning color conversion film and display device applying same
CN103917000A
Preparation method of porous nanofiber non-woven fabric
CN103981633A
Fibre containing nanopore network prepared from high voltage electrostatic spinning and application thereof
CN104689371A
Nanometer luminescent fiber and preparation method thereof
CN106245129A